Gender-Based Differences in EFL Writing: Linguistic Features in Indonesian High School Students’ Narratives - Miftahur Ridha; T. Silvana Sinar, T. Silvana; Zein, T. Thyrhaya (Universitas Lancang Kuning, 2024)
This study uniquely investigates gender-based differences in the linguistic features of narrative texts within the under-researched context of Indonesian high school students learning English as a Foreign Language (EFL). Focusing specifically on narrative writing, this research provides novel insights into how gender influences written expression. Using a qualitative content analysis approach, narrative texts were collected from 20 students (10 male and 10 female) enrolled in a tutoring and English course institution in Indonesia. The texts were analyzed to identify lexicogrammatical features, as outlined by Knapp (2005), with particular attention to the use of action and mental verbs. The findings revealed that male students predominantly used action verbs to describe challenging activities and responsibility, such as